2017
DOI: 10.1021/acsmedchemlett.6b00479
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Novel Allosteric HCV NS5B Inhibitors. 2. Lactam-Containing Thiophene Carboxylates

Abstract: Lomibuvir (1) is a non-nucleoside, allosteric inhibitor of the hepatitis C virus NS5B polymerase with demonstrated clinical efficacy. Further development efforts within this class of inhibitor focused on improving the antiviral activity and physicochemical and pharmacokinetic properties. Recently, we reported the development of this series, leading to compound 2, a molecule with comparable potency and an improved physicochemical profile relative to 1. Further exploration of the amino amide-derived side chain l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…More recently BMS have disclosed their efforts to mitigate undesired PXR activity in one of their series of 11β-HSD1 inhibitors exemplified by 223, Figure 62, 232 which bears some similarities to the triazole series from Merck. Variation of the substitution of the aryl ether had little impact on PXR activation, as shown in Figure 62, with Cl-substitution (224−226) actually increasing PXR activity and fluorine (227) having no impact in this instance. The methylpyridine (228) did bring some benefit, Figure 62.…”
Section: Empirical Medicinal Chemistry Approachesmentioning
confidence: 96%
See 1 more Smart Citation
“…More recently BMS have disclosed their efforts to mitigate undesired PXR activity in one of their series of 11β-HSD1 inhibitors exemplified by 223, Figure 62, 232 which bears some similarities to the triazole series from Merck. Variation of the substitution of the aryl ether had little impact on PXR activation, as shown in Figure 62, with Cl-substitution (224−226) actually increasing PXR activity and fluorine (227) having no impact in this instance. The methylpyridine (228) did bring some benefit, Figure 62.…”
Section: Empirical Medicinal Chemistry Approachesmentioning
confidence: 96%
“…Subsequently, Vertex have disclosed their SAR against PXR for a very similar series, depicted in Figure 52. 227 Using a luciferase reporter gene assay (24 h incubation) in DPX2 cells (a human hepatoma cell line) 180 showed weaker PXR activation than 181, albeit with a similar EC 50 value, showing the chiral center has a marked impact.…”
Section: Empirical Medicinal Chemistry Approachesmentioning
confidence: 99%
“…This core is, indeed, a well-known bioisostere of anilines used in drug design and can be found in agrochemicals such as in dimethenamid [2] and penthiopyrad, [3] showing herbicidal and fungicidal activity respectively, and also in pharmaceuticals like the local anesthetic articaine [4] or telenzepine [5,6] which is used for the treatment of peptic ulcer (Figure 1). Moreover, according to recent studies, this scaffold is present in potent inhibitors of hepatitis C virus [7,8] and tumor growth, [9,10] as well as in anti-inflammatory [11] and anti-microbial [12] compounds.…”
Section: Introductionmentioning
confidence: 99%
“…The computed data showed that keteniminium salts both kinetically and thermodynamicallyundergo electrocyclization more readily than ketenes, allenes, and trienes. Besides, naphthylamines, (benzo)thiophenes, (benzo)furans and indoles are also core scaffolds for several bioactive compounds used in various areas such as agrochemicals, 26 pharmaceuticals, 27 antimitotic agents, 28 inhibitors of tubulin polymerization, 29 tumor growth, 30,31 and antiviral 32,33 compounds (Scheme 2). Our previous study has described an efficient access to 3aminobenzothiophene derivatives through the 6π-electrocyclization of the corresponding KI (Scheme 1b).…”
Section: ■ Introductionmentioning
confidence: 99%